Sex difference in anti‐sperm antibodies. (5th July 2022) - Shibahara, Hiroaki; Chen, Yuekun; Honda, Haruka; Wakimoto, Yu; Fukui, Atsushi; Hasegawa, Akiko
Abstract: Background: Some diseases have sex differences. There have been no reports on the relationship between anti‐sperm antibodies (ASA) and sex differences. Methods: ASA are detected by sperm‐immobilization test using patients' sera in women. In men, the ASA testing is generally performed by direct‐immunobead test. Main findings: Sperm‐immobilizing antibodies in women inhibit sperm migration in their genital tract and exert inhibitory effects on fertilization. ASA bound to sperm surface in men also show inhibitory effect on sperm passage through cervical mucus. The fertilization rate of IVF significantly decreased when sperm were coated with higher numbers of ASA. For women with the antibodies, it is important to assess individual patients' SI50 titers. In patients with continuously high SI50 titers, pregnancy can be obtained only by IVF. For men with abnormal fertilizing ability by ASA, it is necessary to select intracytoplasmic sperm injection. Production of sperm‐immobilizing antibodies is likely to occur in women with particular HLA after exposure to sperm. The risk factors for ASA production in men are still controversial. Conclusion: Attention to sex differences in specimens, test methods and the diagnosis of ASA should be paid. For patients with ASA, treatment strategies have been established by considering sex difference for each.